Isolation and Molecular Detection of Mycoplasma ovipneumoniae and Mycoplasma arginini in Sheep and Goats in Karnataka, India - Karthik, C D; Rathnamma , D; Isloor, Shrikrishna; Veeregowda , B M; Sharada , R; Shivashankar, B P; Sumathi, B R; Sudha , G; Suryanarayan , T (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Mycoplasmosis is one of the economically important diseases in small ruminants. Mycoplasma affects respiratory system predominantly  apart from synovial joints, udder and mucus membrane bearing surface. In the current study, a total of 514 samples consisting of 465  nasal swabs, 18 lung tissues, 16 milk, 11 synovial fluids, 3 ear swabs, and one fetal fluid were subjected for isolation of Mycoplasma in  PPLO broth and PPLO agar. Inoculated samples were incubated at 37°C for 24-48 h under 5% CO2, until turbidity and colour change was  observed. Broth cultures were also subjected for Mycoplasma genus specific and species specific PCR. Of the 514 samples that were  cultured, 32 (6.22%) produced characteristic ‘fried egg’ microcolonies on the agar surface. Of the 32 isolates, 21 were M. ovipneumoniae, 7  were M. arginini and 4 unidentified mycoplasma species. Seventy five (14.59%) samples were positive for genus specific PCR. By species  specific PCR, 21 (28%) samples were identified as M. ovipneumoniae, 13 (17.33%) M. arginini, whereas 41 (54.66) samples did not amplify  with either of the clusters specific primers or other species specific primers and remain unidentified.
Keywords: Karnataka; Mycoplasma isolation; M. arginini; M. ovipneumoniae; PCR; Sheep and goats